ASSESSMENT OF BACTERIOLOGICAL QUALITY OF KILISHI (READY-TO-EAT MEAT PRODUCT) SOLD IN GOMBE, NIGERIA - HUSSEIN, IBRAHIM I.; HANIFA, MOHAMMED; CHRISTY, BABAYO; GIDEON, NELSON H.; KAWUWA, ABUBAKAR N. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Kilishi is a highly relished ready-to-eat meat product processed and sold in most parts of Nigeria. Its consumption cut across diverse cultures, classes and socio-economic status, though it originated and popular in the northern part of the country. However, the common unhygienic method of processing Kilishi depicted by majority of producers has widely queried its microbiological quality and safety for public consumption which prompted this study. This study was aimed at assessing the bacteriological quality of randomly sampled Fifteen (15) Kilishi and its spice mix sold in five (5) different locations within Gombe metropolis. Kilishi samples were subjected to standard microbiological analyses that include serial dilution, viable plate count, culturing on selective and differential media then morphological identification and biochemicalbased characterization of bacterial isolates. Findings revealed higher bacterial count (aerobic mesophilic bacteria) exceeding the minimum allowable limit for a ready-to-eat products thus indicating an unacceptable state of the meat products. Also, coupled with the identification and confirmation of ten (10) diverse bacteria including potentially pathogenic strains (Salmonella typhi, Shigella spp, Staphylococcus aureus, and Pseudomonas aeruginosa, Bacillus cereus), indicators of faecal contamination (Escherichia coli, Klebsiella pneumoniae, Citrobacter freundii) and others. Put together, these showed the low bacteriological quality of Kilishi sold in the outlets studied. Therefore, it is highly recommended that best hygiene measures, good sanitation practices and standard food handling rules be strictly adhered to during processing and post-production stages including packaging. This is paramount to guaranty food safety, prevent any outbreak of food-borne diseases and to importantly safeguard public health.